Análise dos registros do risco de queda em idosos hospitalizados - Silva, Danieli Mota da (2022)
Objective: to analyze the record of the risk of falls in hospitalized elderly. Method: documental research was used in the medical records of the elderly. The study was carried out in a university hospital in southern Brazil, in which elderly patients are admitted. The sample consisted of 190 medical records of patients who met the inclusion criteria, age 60 years or older, with moderate to high risk according to the Morse Fall Scale - Brazilian version - MFS-B within 48 hours of hospitalization, under Registry CAAE number 40092320.3.0000.5336 and opinion number 4,425,364. In the second moment, the collection was carried out only with elderly patients who had a fall notified to the Hospital's Patient Safety Center, during hospitalization through a questionnaire, which totaled 10 patients. Results: The age of the participants had a median of 70 years with a range from 60 years to 93 years. The male sex was predominant. The investigation of falls at home before admission shows that the majority of the elderly had not had a previous fall. The assessment of the risk of falls in the first 24 hours of hospitalization shows that most elderly people had a risk score by MFS-B up to 35 points, indicating moderate risk. When verifying the data related to the risk of falls and/or falls and the recording actions in the medical records, by the professionals involved, low adherence was identified (< 12%), with nurses being the professionals who most adhered to the actions and registration followed. of doctors. Conclusions: It is necessary to take a look at the proper application of any scale, so as not to establish wrong risks that could be confusing for the establishment of an action plan with patients.